Ethanol Dehydrogenase I Contributes to Growth and Sporulation Under Low Oxygen Condition via Detoxification of Acetaldehyde in Metarhizium acridum - Zhang, Erhao; Cao, Yueqing; Xia, Yuxian (Frontiers in Microbiology, 2018)
The entomopathogenic fungi encounter hypoxic conditions in nature and in artificial culture. Alcohol dehydrogenases (ADHs) are a group of oxidoreductases that occur in many organisms. Here we demonstrated that an alcohol dehydrogenase I, MaADH1, in the locust-specific fungal pathogen, Metarhizium acridum, functioned in acetaldehyde detoxification mechanism under hypoxic conditions in growth and sporulation. The MaADH1 was highly expressed in sporulation stage under hypoxic conditions. Compared with a wild-type strain, the ΔMaADH1 mutant showed inhibited growth and sporulation under hypoxic conditions, but no impairment under normal conditions. Under hypoxic conditions, ΔMaADH1 mutant produced significant decreased alcohol, but significant increased acetaldehyde compared to wild type. M. acridum was sensitive to exogenous acetaldehyde, showing an inhibited growth and sporulation with acetaldehyde added in the medium. MaADH1 did not affect virulence. Our results indicated that the MaADH1 played important roles in growth and sporulation under hypoxic stress by detoxification of acetaldehyde in M. acridum.